2020
DOI: 10.1002/cbin.11443
|View full text |Cite
|
Sign up to set email alerts
|

ACADSB regulates ferroptosis and affects the migration, invasion, and proliferation of colorectal cancer cells

Abstract: Colorectal cancer (CRC) is one of the most pressing health issues in today's society. As such, it is imperative that the scientific community devise effective methods to inhibit the proliferation and metastasis of CRC cells. Ferroptosis is a recently discovered regulatory cell death mode mainly manifested by dysregulation of cellular iron metabolism and mitochondrial lipid peroxidation. ACADSB is a member of the acyl-CoA dehydrogenase. This study finds that ACADSB is lowly expressed in CRC tissues. Its express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…e potential mechanisms analysis also supported that more tumor metastasis-associated pathways were activated in high-score samples. Previous studies also proved that ferroptosis can affect tumor migration and invasion including colorectal cancer [45], melanoma [46], breast cancer [47], prostate tumor [48], and so on. Collectively, this work proposed that the activation of ferroptosis may affect ovarian cancer progression by modulating tumor metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…e potential mechanisms analysis also supported that more tumor metastasis-associated pathways were activated in high-score samples. Previous studies also proved that ferroptosis can affect tumor migration and invasion including colorectal cancer [45], melanoma [46], breast cancer [47], prostate tumor [48], and so on. Collectively, this work proposed that the activation of ferroptosis may affect ovarian cancer progression by modulating tumor metastasis.…”
Section: Discussionmentioning
confidence: 89%
“…Cell transfection was performed by ENO3 and GPX4 lentiviral transfection harboring with overexpressed (OE) or short hairpin RNA (shRNA) plasmid of ENO3 and GPX4 as previously described (26). Briefly, L02 cells at a density of 3×10 5 cells/well were seeded in a six-well plate prior to transfection.…”
Section: Cell Transfectionmentioning
confidence: 99%
“…It has been proved that resistance to ferroptosis reduced the efficacy of sorafenib and was associated with poor prognosis in hepatocellular carcinoma ( Houessinon et al, 2016 ; Liang et al, 2020 ). Lu et al reported that ferroptosis was suppressed in colorectal cancer, leading to short overall survival of colorectal cancer patients ( Lu et al, 2020 ). Similarly, ferroptosis plays an important role in breast cancer.…”
Section: Introductionmentioning
confidence: 99%